Effects of Extrinsic Wheat Fiber Supplementation on Fecal Weight; A Randomized Controlled Trial - Beate Brandl (Nutrients, 2020)
Higher fiber intake may confer beneficial effects on health. Our objective was to investigate the impact of 10 g extrinsic wheat fiber on fecal bulk. Therefore, we performed two randomized intervention studies in which we provided extrinsic wheat fiber-enriched products or appropriate control products for five days together with normal diet. In one trial, 10 participants received fiber-enriched food products, whereas in the second study, 19 participants supplemented their daily diet with fiber-enriched drinks. The main outcome variable of this intervention was fecal bulk. Other outcomes were gut microbiota composition, short chain fatty acids in feces, and stool consistency and frequency. Fecal wet weight was significantly increased (p < 0.02) with extrinsic wheat fiber-enriched foods. In contrast, ingestion of extrinsic wheat fiber in the form of drinks did not significantly change fecal wet weight. In both groups, fecal dry weight was not altered upon extrinsic wheat fiber supplementation. However, the intake of fiber-enriched foods resulted in higher acetic acid levels in feces compared to fiber-enriched drinks. Regarding gut microbiota profiles, extrinsic wheat fiber-enriched food products were not associated with substantial alterations. In conclusion, 10 g extrinsic wheat fiber added to a normal diet increased fecal bulk if administered in a solid food matrix, but not if applied in the form of drinks. DRKS, DRKS00015792.Registered 30 October 2018.